Proceedings of the Conference on Applications, Technologies, Architectures, and Protocols for Computer Communication 2000
DOI: 10.1145/347059.347549
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic model of TCP/IP with stationary random losses

Abstract: Abstract-In this paper, we present a model for TCP/IP congestion control mechanism. The rate at which data is transmitted increases linearly in time until a packet loss is detected. At this point, the transmission rate is divided by a constant factor. Losses are generated by some exogenous random process which is assumed to be stationary ergodic. This allows us to account for any correlation and any distribution of inter-loss times. We obtain an explicit expression for the throughput of a TCP connection and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
182
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(189 citation statements)
references
References 22 publications
7
182
0
Order By: Relevance
“…Every rounds, the window size of the cumulative flow is increased by , and we have (10) Assuming that and are mutually independent sequences of i.i.d. random variables (as in [1]), from (9) we have (11) Taking into account the assumption that a loss occurs identically distributed over all flows we can say that and are equal for all flows, and from now on we denote them by and . From (2) and (5), we have (12) We assume that at the end of a TD-period , flows experiencing loss in that TDP have the window size , and other flows that experience loss in the previous loss event have the window size , etc.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Every rounds, the window size of the cumulative flow is increased by , and we have (10) Assuming that and are mutually independent sequences of i.i.d. random variables (as in [1]), from (9) we have (11) Taking into account the assumption that a loss occurs identically distributed over all flows we can say that and are equal for all flows, and from now on we denote them by and . From (2) and (5), we have (12) We assume that at the end of a TD-period , flows experiencing loss in that TDP have the window size , and other flows that experience loss in the previous loss event have the window size , etc.…”
Section: Modelmentioning
confidence: 99%
“…From (2) and (5), we have (12) We assume that at the end of a TD-period , flows experiencing loss in that TDP have the window size , and other flows that experience loss in the previous loss event have the window size , etc. The mean value of the window size of the cumulative flow is (13) From (11)- (13), we have (14) From (10), assuming that a loss occurs independently distributed over the size of the cumulative window in a loss round, hence , we have (15) and including (6), (8), (11), (12), and (14) (16) Solving this equation for , we get (17), shown at the bottom of the page, and including (14), we get (18), shown at the bottom of the page. From (1), (2), (6), (8), and (17), we have (19), shown at the bottom of the page.…”
Section: Modelmentioning
confidence: 99%
“…This situation is quite common in wireless channels in which radio conditions are often the bottlenecks, and not the congestions. It is also a common situation in TCP connections over long distances as was shown by experiments in [3]. In addition, when connections are subject to loss events by exogenous traffic, it has been shown that the losses are independent of the window size (as has been observed in [5]).…”
Section: Introductionmentioning
confidence: 77%
“…Upon loss detection, the window is reduced by a multiplicative factor. TCP modeling has been studied extensively in the literature (see e.g., [2][3][4] and references there), and many authors have been interested in the performance of several parallel TCP connections (see e.g., [5][6][7]). …”
Section: Introductionmentioning
confidence: 99%
“…For recent papers on growth-collapse models and their applications, see [1], [2], [3], [5], [6], [8], [9], and the references therein.…”
Section: Introductionmentioning
confidence: 99%